Conservation Value Of A Living Heritage Site On Penang Island, Malaysia - Lilian, Chan Mei Li (2009)

(untitled)
George Town is the capital of Penang Island, a town of rich and diverse history which reflect the cultures brought by the trade-winds since the 18th century. Many of the heritage buildings and the businesses or activities, that took place within them still survive until today, many of which involve skills passed down through the generations, making George Town a town with a ‘living’ heritage. The objectives of this study were to estimate the value of Penang Island households’ willingness to pay for the conservation of a living heritage in George Town, and to identify the determinants of the willingness-to-pay. This study aimed to add to the scarce literature of this type of research, and reduce the dependence on benefit transfers for cultural heritage goods, which are often sitespecific, and therefore unsuitable.The Stated Preference (SP) method of Contingent Valuation (CV) was applied in this study, concentrating on the living heritage existing within inner George Town, covering about 3,700 pre-colonial shophouses. A total of 320 in-person interviews of citizens of Penang Island were conducted in the first-quarter of 2006, out of which 283 questionnaire responses were usable. The results showed that the Contingent Valuation Method (CVM) can be successfully applied to value a living cultural heritage in Penang Island, where the mean willingness-to-pay for the conservation of inner George Town’s living heritage is about RM94.50 as a once-off contribution amount. The results showed that attitudinal aspects like interest and concern for the condition of the ‘living’ heritage play an important factor in the probability that respondents would be willing-to-pay for its conservation, together with the respondents’ level of income. Behavioural aspects like knowledge regarding the heritage, frequency of visits, and emotional regard for the heritage are not significant to the probability that the respondents would be willing to contribute towards the heritage conservation. The results of this research can be used by policy-makers and NGOs to rank the importance of conserving the ‘living’ heritage relative to competing projects, and help improve the management of heritage conservation and resource allocation.